Spanglish - Brooks, James L.; Sakai, Richard; Ansell, Julie; Sandler, Adam.; Leoni, Tea 1966-.; Vega, Paz 1976-.; Leachman, Cloris; Bruce, Shelbie; Steele, Sarah; Hyland, Ian.; Luna, Victoria; Seale, John 1942-.; et al. ([Culver City, Calif.] Columbia Pictures Sony Pictures Home Entertainment, 2005)
When Flor and her daughter Christina come to the United States from Mexico, Flor gets a job as a maid at the home of successful chef John Clasky, his insecure wife Deborah, their two children, and Deborah's mother. When they move in with the Claskys for the summer, Flor discovers that life in a new country can be challenging in more ways than one.
Originally released as a motion picture in 2004.
Adam Sandler, Tea Leoni, Paz Vega, Cloris Leachman, Shelbie Bruce, Sarah Steele, Ian Hyland, Victoria Luna.
VCD.
Keywords: Families -- California -- Los Angeles -- Drama; Women domestics -- California -- Los Angeles -- Drama; Mothers and daughters -- California -- Los Angeles -- Drama; Feature films